Les hérétiques savent-ils écrire ? Les hérésiologues « critiques littéraires » de leurs adversaires. - Ribreau, Mickaël (Vigiliae Christianae, 2019)
Deconstructing one's adversary's image is a traditional tool of judicial rhetoric. Cicero, for example, represents adversaries as illiterate, unable to write or speak. The heresiologists, as Jerome or Augustin, could have been influenced by this strategy. They ask, Do the heretics know how to write ? Their answers vary according to which authors they have in mind and which text genre they use. In the Catalogue of Famous Men Jerome emphasizes the heretics' literary talent, because of the genre in which he is writing, but also since they are dead. In his polemical works, influenced by judicial speech, he represents the relevant heretic as unable to write, because, as a heretic, he is unable to do anything, and because he is outside the church ; by deconstructing the heretic's image, Jerome wants to avoid the others to be contamined by heresy. For Augustine, the heretic can write well, even too well ; and for him the problem is precisely that. Augustin emphasizes the heretic's skill to highlight the heretic's danger, caused by his eloquence.